Radiation exposure of the Army of the FR Yugoslavia in Kosovo and Metohia during the NATO aggression of 1999 - Anđelković-Lukić, Mirjana (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: The paper indicates the radiation doses the military personnel of the Federal Republic of Yugoslavia were exposed to, and in particular the military personnel of the motorized brigades in the territory of Kosovo and Metohia on the Albanian-Yugoslav border.Methods: Gammaspectrometry measurements have confirmed that round penetrators contained depleted uranium, and the presence of alpha, beta and gamma radiation was determined by the method of dosimetric measurement.Results: The use of ammunition with 238U depleted uranium, with added plutonium, pollutes the environment, water, and soil in the long term, causing various disorders and diseases, primarily malignant ones. The radioactivity of 239Pu, compared to its toxicity, is several thousand times higher and the inhalation of plutonium dust is harmful and causes cancer. Uranium is a pyrophoric metal, toxic, radioactive and easy to ignite. Its oxides are toxic and partially soluble in water. After ignition, the round releases radioactive aerosol particles which burn in contact with the air causing short or long term damage wheninhaled. In Kosovo and Metohia, a large amount of radioactivity was measured during the NATO aggression against the FR Yugoslavia. In Metohia, radioactivity was 1,100 times that of natural background radiation.Conclusion: During the war, the Army of the FR Yugoslavia was exposed to high radioactive doses, so that among the members of the army after the war there was an increased incidence of various malignancies, many of them lethal.
Keywords: chemical warfare; depleted uranium ammunition; increased radioactivity; chemotoxicity; plutonium; exposure of the Army of the FR Yugoslavia to radiation; disease; malignancy